STOCK REACTIONS AND ABNORMAL STOCK RETURNS IN THE PROPERTY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE DUE TO THE COVID-19 PANDEMIC - Aloysius Van Rhein Tambunan; Gracia S. Ugut (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The COVID-19 outbreak has severely affected equity markets and most stock index around the world. Indonesia is no exception, the social restriction policy (PSBB) imposed by the government caused the IHSG to be corrected negatively. One of the sectors that was severely affected at the beginning of the pandemic was the property sector. This study aims to see the reaction of property sector stocks due to the Covid-19 incident and abnormal returns that occurred during the early days of the Covid-19 pandemic. The research sample is 51 property sector companies listed on the IDX. By using multivariate regression, it was found that the announcement of the first time an Indonesian citizen had contracted Covid-19 was still responded positively by stock returns in the property sector. Meanwhile, the announcement of the restriction policy (PSBB) for the first time in Jakarta encountered a negative response by stock returns in the property sector. The abnormal return model shows that company size, cash/TA, leverage, BVPS, and market to book value altogether significantly affect the cumulative abnormal return of property sector stocks, with a contribution of 18.07%. While partially only the size of the company that significantly affects the cumulative abnormal return of the property sector. Therefore, the larger the size of the company, the greater the abnormal return. Keywords: Covid-19 Stock Reaction, Abnormal Returns, Multivariate Regression